Increasing the Magnesium Concentration in Various Dialysate Solutions Differentially Modulates Oxidative Stress in a Human Monocyte Cell Line - Carmen Vida; Julia Carracedo; Patricia de Sequera; Guillermo Bodega; Rafael Pérez; Matilde Alique; Rafael Ramírez (MDPI AG, 2020)
Oxidative stress is exacerbated in hemodialysis patients by several factors, including the uremic environment and the use of dialysis fluids (DFs). Since magnesium (Mg) plays a key role in modulating immune function and in reducing oxidative stress, we aimed to evaluate whether increasing the Mg concentration in different DFs could protect against oxidative stress in immunocompetent cells in vitro. Effect of ADF (acetate 3 mM), CDF (citrate 1 mM), and ACDF (citrate 0.8 mM + acetate 0.3 mM) dialysates with Mg at standard (0.5 mM) or higher (1, 1.25, and 2 mM) concentrations were assessed in THP-1 monocyte cultures. Reactive oxygen species (ROS) and malondialdehyde (MDA) levels were quantified under basal and uremic conditions (indoxyl sulfate (IS) treatment). Under uremic conditions, the three DFs with 0.5 mM Mg promoted higher ROS production and lipid damage than the control solution. However, CDF and ACDF induced lower levels of ROS and MDA, compared to that induced by ADF. High Mg concentration (1.25 and/or 2 mM) in CDF and ACDF protected against oxidative stress, indicated by reduced ROS and MDA levels compared to respective DFs with standard concentration of Mg. Increasing Mg concentrations in ADF promoted high ROS production and MDA content. Thus, an increase in Mg content in DFs has differential effects on the oxidative stress in IS-treated THP-1 cells depending on the dialysate used.